Effects Of Lower Limb Muscle Training Strategies To Improve The Exercise Endurance Of Moderate Copd Patients - Muthukumar, T.S.; Ramachandran, Arunachalam; V, Anandh; Duraisamy, Anandan (Journal of Neonatal Surgery, 2025)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a progressive lung disease characterized by airflow limitation and skeletal muscle dysfunction, particularly in the lower limbs, contributing to reduced exercise tolerance. Pulmonary rehabilitation, including lower limb muscle training, has been shown to enhance physical endurance in COPD patients. Objective: This study aimed to evaluate the effectiveness of lower limb muscle training strategies, alongside conventional chest physiotherapy, in improving exercise endurance and quality of life in patients with moderate COPD. Methods: A total of 60 patients with moderate COPD, aged 45–65 years, were enrolled and randomly divided into two groups (n=30 each). Group A (Experimental) received lower limb training using a cycle ergometer three times per week for 12 weeks, along with conventional chest physiotherapy and breathing exercises. Group B (Control) received only conventional chest physiotherapy. Exercise endurance and quality of life were assessed using the 6-Minute Walk Test (6MWT), Five-Repetition Sit-to-Stand Test (5STS), and Clinical COPD Questionnaire (CCQ), measured at baseline, 4th, 8th, and 12th weeks. Paired and unpaired t-tests were used for statistical analysis. Results: Group A showed a statistically significant improvement in 6MWT distance and 5STS time compared to Group B (p < 0.05). CCQ scores also demonstrated marked enhancement in quality of life in the experimental group. These findings suggest that lower limb muscle training improves functional capacity and reduces symptoms in moderate COPD patients. Conclusion: Lower limb muscle training as part of a structured pulmonary rehabilitation program significantly enhances exercise endurance and quality of life in patients with moderate COPD. Incorporating such training into standard physiotherapy practices may improve clinical outcomes